DAMPAK PEMBANGUNAN BANDARA TRUNOJOYO SUMENEP TERHADAP PEREKONOMIAN MASYARAKAT SEKITAR BANDARA TRUNOJOYO SUMENEP - Rofik, Mohammad; Arifin, Miftahol; Liyanto, Liyanto (Universitas Muhammadiyah Parepare, 2020)
Economic growth is always synonymous with development, it is impossible for economic growth to be achieved without going through development. Development should have an impact on improving the economic order, especially increasing production capacity. If not, development will not benefit at all. This study aims to see the impact caused by airport construction for the community around the airport. The data were collected through respondents on a Likert scale with the sample taking technique using the roscoe formula which said the number of samples was at least 10 times of the number of variables. The sample in this study is 50 x 2 = 100 respondents, were determined by purposive sampling technique. The data analysis technique used simple linear regression analysis, with hypothesis testing is t test and determination coefficient test. The results of the analysis explain that airport development have a positive effect and significant on economy of the community.Economic growth is always synonymous with development, it is impossible for economic growth to be achieved without going through development. Development should have an impact on improving the economic order, especially increasing production capacity. If not, development will not benefit at all. This study aims to see the impact caused by airport construction for the community around the airport. The data were collected through respondents on a Likert scale with the sample taking technique using the roscoe formula which said the number of samples was at least 10 times of the number of variables. The sample in this study is 50 x 2 = 100 respondents, were determined by purposive sampling technique. The data analysis technique used simple linear regression analysis, with hypothesis testing is t test and determination coefficient test. The results of the analysis explain that airport development have a positive effect and significant on economy of the community.